2003
DOI: 10.1097/01.asn.0000068460.37369.dc
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of IgA Nephropathy with ACE Inhibitors

Abstract: Abstract. Some retrospective studies have suggested a beneficial influence of angiotensin-converting enzyme (ACE) inhibitors on the progression of IgA nephropathy (IgAN), but prospective and controlled studies demonstrating this effect are lacking. Forty-four patients with biopsy-proven IgAN, proteinuria Ն 0.5 g/d, and serum creatinine (SCr) Յ 1.5 mg/dl were randomly assigned either to receive enalapril (n ϭ 23) or to a control group (n ϭ 21) in whom BP was controlled with antihypertensives other than ACE inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
196
0
7

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(210 citation statements)
references
References 26 publications
7
196
0
7
Order By: Relevance
“…While our enrollment was proceeding slowly, because ACE-I therapy was becoming a widely used treatment for patients with IgAN (even though not supported by evidence-based medicine), another group was performing an RCT in adults; this was published by Praga et al (26) in 2003. Compared with this study, our report has the advantages of being a placebocontrolled study (this is the first placebo-controlled RCT in IgAN), of being multicenter based, and of having well-defined selection criteria.…”
Section: Discussionmentioning
confidence: 99%
“…While our enrollment was proceeding slowly, because ACE-I therapy was becoming a widely used treatment for patients with IgAN (even though not supported by evidence-based medicine), another group was performing an RCT in adults; this was published by Praga et al (26) in 2003. Compared with this study, our report has the advantages of being a placebocontrolled study (this is the first placebo-controlled RCT in IgAN), of being multicenter based, and of having well-defined selection criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Proposed therapies include corticosteroids (8 -20), fish oil (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31), and angiotensin-converting enzyme (ACE) inhibitors (32,33). Although some studies of corticosteroids and omega-3 fatty acids (O3FA) have reported significant benefit, others showed no apparent benefit.…”
mentioning
confidence: 99%
“…Possible explanations for the variable outcomes in patients who were treated with fish oil supplements include differences in the patient populations and variations in the dose or composition of the fish oil used. ACE inhibitors have been helpful in patients with a wide assortment of glomerulopathies, including patients with IgAN (32,33). This study was designed to evaluate whether a 2-yr course of alternate-day prednisone or of daily O3FA on a background of ACE inhibitor therapy in hypertension patients provides an effective means of preventing deterioration of GFR in young patients with IgAN.…”
mentioning
confidence: 99%
“…cyturia using immunosuppressive drugs is unmatched by data from ACEI studies ( Figure 1). Only two randomized, controlled trials detailed prevalent BP: in our study of immunosuppressive drugs, mean arterial pressure (MAP), matching in both cohorts at 101 mmHg, was 135/85 or 140/80, 1 remarkably equal to levels achieved in the ACEI study 12 ; pressures in both were Ͻ10% above current recommendations: MAP 92 (125/75). However, the benefits of BP control, more so using ACEI and/or angiotensin receptor blockers (ARB), have an event ratio effect in preserving renal function in IgAN an order of magnitude lower than those of a combined immunosuppressive regimen (Table 1).…”
mentioning
confidence: 72%
“…ACEI do not improve erythrocyturia, 12 and, typically, proteinuria is reduced only 50 to 70% with ACEI or combined ACEI/ARB, 13 reversing on withdrawal (Table 1). This striking contrast seems powerful confirmation that only immunosuppressive drugs can induce clinical remission in IgAN.…”
mentioning
confidence: 99%